Revitalizing Cultural Heritage Buildings to Enrich Urban Tourism Experiences: A Qualitative Case Study in Jakarta - Heryanti Utami; Felina C. Young (International Journal of Management and Economic Research (IJOMER), 2025)
This study explores how the use of Cultural Heritage Buildings (CHBs) in Jakarta contributes to enriching the experiential dimensions of urban heritage tourism. While the conservation of cultural assets has traditionally been viewed through a preservationist lens, this study adopts a qualitative approach to examine how these spaces are creatively revitalized into experiential venues that appeal to modern urban tourists. By employing descriptive case studies of six iconic CHBs—Pos Bloc, Sarinah, Paser Baroe, Gedung Kesenian Jakarta, Monumen Nasional, and Museum Nasional Jakarta—this research analyzes how sensory, emotional, cognitive, behavioral, and relational experiences are co-constructed through strategic reuse and experiential marketing. Data were collected through site observations, expert documentations, and interpretive analysis of urban narratives. Findings show that the unique combination of historical ambiance, commercial adaptation, and cultural storytelling creates a multidimensional experience that goes beyond visual aesthetics. Jakarta’s approach demonstrates how CHBs can serve both as heritage anchors and platforms for innovative urban cultural expression. The study concludes with recommendations for urban tourism developers and heritage managers to align cultural sustainability with tourism innovation.